2018
DOI: 10.3390/proteomes6020018
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Extracellular Proteome of the Emerging Pathogen Corynebacterium ulcerans

Abstract: Corynebacterium ulcerans is an emerging pathogen, which is increasingly recognized as an etiological agent of diphtheria, but can also evoke ulcers of the skin and systemic infections in humans. Besides man, the bacteria can colonize a wide variety of different animals, including cattle and pet animals, which might serve as a reservoir for human infections. In this study, surface-located proteins and the exoproteome of two Corynebacterium ulcerans strains were analyzed, since these may have key roles in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…Extracellular proteins were prepared as described [ 31 ]. Cells were removed by centrifugation (10 min, 4 °C, 4000× g ) and the supernatant was subsequently filtered using a 0.2 µm pore size filter (Minisart, Sartorius, Göttingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular proteins were prepared as described [ 31 ]. Cells were removed by centrifugation (10 min, 4 °C, 4000× g ) and the supernatant was subsequently filtered using a 0.2 µm pore size filter (Minisart, Sartorius, Göttingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For isolation of cell surface proteins by tryptic shaving [ 31 , 45 ] independent batches of cells were harvested and treated with 1.5 µg sequencing grade trypsin (Promega, Madison, WI, USA) for 1.5 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of pathogenic corynebacterial species, the repertoire of secreted and surfaceexposed proteins, the exoproteome, have been documented because of their potential to act as antigenicity and virulence factors, since these molecules are promptly exposed to the host cells, making they are suitable for the use of vaccine and drug targets. A recent study investigated both surface and extracellular proteome of two C. ulcerans strains, where NanoLC-MS/MS was performed to analyze the set of proteins, which were similar expression patterns of putative virulence factors [72].…”
Section: Proteomicsmentioning
confidence: 99%
“…From a 2006 proteomics study 9 of C. diphtheriae using 2D gel electrophoresis separation of C. diphtheriae proteins, 85 surface and secreted proteins were identified. However, more recent studies on Corynebacterium ulcerans and Corynebacterium glutamicum identified many more proteins on or predicted to be localized to the cell surface, [10][11][12] suggesting that more coverage of the secreted and cell surface C. diphtheriae proteome should be obtainable. We used a high resolution HPLC mass spectrometry experimental strategy (e.g., trypsin digestion of precipitated supernatant and intact cells) to obtain an updated secretome and surfaceome of C. diphtheriae.…”
Section: Introductionmentioning
confidence: 99%